Text compaction for display on very small screens - Corston-Oliver, Simon (Association for Computational Linguistics, 2001)
Very small screens, such as the LCD displays on cellular telephones, pose unique problems for the display of textual messages. This paper presents a collection of techniques used to compact email text for display on mobile devices. These techniques range from simple string manipulations to more sophisticated linguistic processing. The techniques have been implemented in a commercial product for four languages: English, French, German and Spanish.